Shining a light on parasite behaviour: daily patterns of Argulus fish lice. Issue 7 (11th June 2021) - Hunt, Rhi; Cable, Jo; Ellison, Amy
Abstract: Abstract: Parasites display a wide range of behaviours that are frequently overlooked in favour of host responses. Understanding these behaviours can improve parasite control through a more precise application or development of new behaviour-based strategies. In aquaculture fish lice are an ongoing problem, infections reduce fishery production and control options are limited. Fish lice are distinct in their ability to survive and swim off hosts, allowing the transmission to multiple fish hosts across their lifespan. Here we assessed the off-host behaviour of Argulus foliaceus (a freshwater fish louse) and observed a diurnal rhythmical pattern in their behaviour. This pattern was lost when lice were exposed to constant darkness, indicating that the behaviour is not endogenously driven. Males were consistently active in light with reduced activity in darkness. In contrast, females were active during light and dark phases with peak activity at the start of dark periods. A. foliaceus was also strongly attracted to a light stimulus, preferring white- and blue-coloured lights over green- or red-coloured lights. Light is a strong driver of fish louse activity and could be used to trap parasites. Aquaculture light regimes could also be altered to reduce parasite attraction and activity.